THE Pengaruh Profitabilitas, Likuiditas dan Corporate Governance Terhadap Pengungkapan Sustainability Report dengan Ukuran Perusahaan sebagai Variabel Moderating - Iqbal Ramadhan, M; Nasir, Azwir; Indrawati, Novita (Program Studi Manajemen FEBM UMRAH, 2023)
This study aims to examine and analyze the effect of profitability, liquidity, the audit committee and the board of directors on the disclosure of the sustainability report with firm size as a moderating variable. The population of this research are basic materials and energy companies listed on the Indonesia Stock Exchange in 2018-2020. The sample selection was done by using purposive sampling, the number of samples was 57 companies. Data analysis using SPSS version 25 software. The results of this study indicate that profitability, liquidity, audit committee and the board of directors have a significant influence on the disclosure of the sustainability report. The size of the company is able to strengthen the influence of profitability and the board of directors on the disclosure of the sustainability report, but cannot moderate the effect of liquidity and the audit committee on the disclosure of the sustainability report.